Alkali-resistant glass fiber high strength concrete and its durability parameters. (2021) - Paktiawal, Ajmal; Alam, Mehtab
Abstract: The use of glass fiber in ordinary and standard concrete had been extensively investigated. Not much research work had been done on high-strength concrete with glass fiber. This research work deals with experimental investigations on the performance of alkali-resistant glass fiber of 12 mm standard cut length with varying percentages of 0.8, 1.2, 1.6, 2.0, and 2.4 by weight of cement in high-strength concrete. Investigations are conducted on fresh concrete for workability and hardened concrete specimens for compressive and tensile strengths, NDT, percent voids and sorptivity after 7 and 28 days of normal curing. It has been observed that the effect of the dose of the fiber on the workability of high strength concrete is similar to its effect on ordinary and standard grade concretes but different for compressive strength. The lower percentage of glass fiber significantly enhances strains without contributing to strength. The higher percentage of the fiber decreases the strength with a lesser increase in corresponding strain than GFRC with a lower percentage of the fiber. The percentage of the fiber which enhances its compressive strength imparts maximum tensile strength to the fibrous concrete after 28 days by 12.24, 13.13, 17.31, 15.82, and 11.94% for the fiber content of 0.8, 1.2, 1.6, 2.0, and 2.4% than non-fibrous concrete. The addition of glass fiber ranging from 0.8% to 2.4% increases the cumulative rate of water absorption and coefficient of sorptivity by 50.0, 54.9, 69.8, 92.1, and 90.6%, and 12.9, 36.3, 34.7, 55.6, and 95.1%, respectively as compared to non-fibrous concrete.